PERAN PENDIDIKAN TERHADAP EKSISTENSI KEHIDUPAN MASYARAKAT ADAT KAMPUNG NAGA, TASIKMALAYA, JAWA BARAT - Kurniawan, Itok Dwi; Suryono, Hassan (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
One of the most important aspects of life is education, thinking and human behavior along with the education has been taken. Education is one of the most important efforts for a nation in maintaining its existence. The purpose of this research is study the role of education to the existence the custom society of Kampung Naga, Tasikmalaya, West Java. This research is a qualitative research with descriptive qualitative method. The data used in the form of qualitative data. Data collection techniques used are observation and literature review. The data analysis techniques using interactive models. The results of research is shown that the important of education role to existence for custom society life of Kampung Naga, Tasikmalaya, West Java. It is shown that the role of education provides more usefulness, but does not change their behavior. There is not only formal education that already exists but also balanced with environmental education in the form of education from family. This education is done so that they can teach the pattern of hereditary behavior that has existed from an early age so that their existence will still survive. They is custom society is not easy along the formal and custom so there are some problems about education. The role of Tasikmalaya Regency Government to encourage indigenous Kampung Naga community for formal education needs to be improvedKeywords: Education, Custom Society